ANALISIS KEBERLANJUTAN USAHA SAPI PERAH DI KECAMATAN NGANTANG KABUPATEN MALANG - Adi Sutanto; Listiari Hendraningsih (Jurnal Gamma, 2011)
Adi Sutanto1 & Listiari Hendraningsih21 & 2Staf Pengajar Jurusan Teknologi Industri Peternakan , Fakultas Pertanian PeternakanUniversitas Muhammadiyah MalangAlamat Korespondensi : Jl. Raya Tlogomas, No.246 MalangEmail: adisutanto@yahoo.comABSTRACTThis study aimed to identify the dimensions of ecology and breeding, economic, social, cultural,and technological infrastructure, legal and institutional. And to achieve the research objectives, theresearch is directed at the target qualitative descriptive and explanatory goals, and the type of researchconducted survey research.The results of sustainability research efforts in the area of dairy cattle showed a relativelymoderate conditions, in detail indicated that: the ecology and breeding, agro-climatic suitability indicator,land for other crops, and land management for lingkunngan can be considered high. which meansnot cause problems. Sustainability Indicators in the economic dimension has average category,which means that the business community developed dairy farmers are not too conducive to creatinga system of highly competitive agribusiness, capable of responding to market dynamics effectivelyand efficiently. Considered the cultural dimension of social roles and patterns of public relations inthe dairy business activities categorized high. Dimensions infrastructure and tekonolgi show stillneeds the role of technology and adequate infrastructure according to the needs of dairy farmers.Legal and institutional aspects of the low where the role of education, banking and microfinance aswell as the involvement of farmer groups is very less.